Association of Paraoxonase-1 (p.L55M) and Paraoxonase-2 (p.S311C) polymorphisms with coronary artery disease in North Indian Punjabi population - Bhat, Mohd Akbar; Singh, Jatinder; Lone, Ghulam Mohd; Goyal, Shiwali (Frontiers in Endocrinology, 2025)
BackgroundParaoxonases (PONs) are a unique family of calcium-dependent enzymes which are tightly associated with the high-density lipoprotein cholesterol (HDL-C), plays a crucial role in protecting the low-density lipoprotein cholesterol (LDL-C) from oxidation, thereby providing protection against atherosclerosis-a key factor for the pathogenesis of coronary artery disease (CAD). The activity of PON enzymes is influenced by genetic polymorphisms in the PON genes. The present case-control study was performed to investigate the association of PON1 (p.L55M, rs854560) and PON2 (p.S311C, rs7493) polymorphisms with CAD in the North Indian Punjabi population.Methods and resultsThe present study included 211 CAD patients and 260 healthy controls genotyped using the polymerase chain reaction-reaction fragment length polymorphism (PCR-RFLP) technique. Binary logistic regression analysis revealed that the SC and CC genotypes of the PON2 (p.S311C) conferred 2-and 3.5-folds increased risk for CAD (OR: 2.03, 95%CI: 1.36-3.01, p=0.001; OR: 3.49, 95%CI: 1.86-6.55, p=0.001, respectively). Moreover, the dominant (OR: 2.29, 95%CI: 1.58-3.32, p=0.0001), co-dominant (OR: 1.62, 95%CI: 1.11-2.36, p=0.012), recessive (OR: 2.58, 95%CI: 1.41-4.72, p=0.001), and log-additive (OR: 1.92, 95%CI: 1.46-2.54, p=0.0001) are the best-fit inheritance models to predict the susceptible gene effects. Furthermore, the LC haplotype (PON1 and PON2) was found to be significantly and independently associated with the increased risk of CAD (OR: 2.34, 95%CI: 1.65-3.32, p=0.0001).ConclusionsOur results indicate a significant and independent association of PON2 (p.S311C) polymorphism with CAD even after gender stratification in North Indian Punjabi population.